Social skills training : for children and adolescents with Asperger syndrome and social-communication problems - Baker, Jed. 4 0 16; Myles, Brenda Smith; 5 (Shawnee Mission, Kansas : Autism Asperger Publishing Company, 2004)
Presents seventy individual skill lessons and activities designed to help students with Asperger syndrome and social-communication problems improve their social skills and learn acceptable behaviors in various situations.
Includes bibliographical references.
Adult.
Keywords: 2 -- 0; 6; Rehabilitation.;Education.;Rehabilitation.;Education. -- Autistic children;Asperger's syndrome.;Social skills in children.;Autistic children;Exceptional children;Asperger's syndrome.;Social skills.;Exceptional children; 20; 2